Edward Snowden, Frenemy of the State. - Tarzie (American Journal of Economics & Sociology, 2017)
The Edward Snowden whistleblowing event is a calculated spectacle of pseudo-dissidence that has more in common with Hollywood-produced propaganda than with genuine whistleblowing. This article presents evidence that Snowden has lied on a number of occasions, calling his credibility into question. Nothing that Snowden has revealed was truly a secret, since several previous whistleblowers had reported, since 2002, about illegal mass surveillance of American citizens by the National Security Agency. Snowden's most striking difference from other NSA whistleblowers is the warm embrace from mainstream media, which has made him a celebrity. The 1998 theatrical film Enemy of the State contained the same sorts of revelations offered by Snowden, and imparts a number of messages to its audience about the security state that are strikingly similar to recurring messages in the Snowden Affair. Since that movie was made with assistance from the CIA these similarities are important to considering how authentic and socially useful his whistleblowing is. It seems evident from Snowden's support for the renewal of the Patriot Act (now the Freedom Act), that he objectively serves the interests of the surveillance state, rather than the public it spies upon.